Applicability study of the photofission based nuclear material isotopic composition measurement method on the Thorium-Uranium system. (December 2017) - Kimura, Rei; Sagara, Hiroshi; Chiba, Satoshi
Abstract: A principle of new nondestructive assay (NDA) technique based on the photofission reaction ratio (PFRR) has been developed, which is aimed at measuring the isotopic composition of nuclear fuel materials without relying on their self-generated neutron information. The feasibility of the PFRR method was validated in the 235 U- 238 U system previously. However, applicability of the PFRR method in the other material is not yet validated. In this study, applicability of PFRR method to the 232 Th- 233 U system was confirmed, PFRR method showed good reproducibility of predicted value of 232 Th and 233 U isotopic composition.